What Determines That Older Adults Feel Younger Than They Are? Results From a Nationally Representative Study in Germany - Heimrich, Konstantin G.; Prell, Tino; Schönenberg, Aline (Frontiers in Medicine, 2022)
Background: There is increasing evidence that subjective age is an important predictor of beneficial health outcomes besides chronological age. However, little is known about the factors associated with younger subjective age. This study aimed to identify which factors are predictive of feeling younger in old age. In this context, feeling younger was defined as an individual’s perception of being younger than their current chronological age. Methods: Data from 4,665 community-dwelling older people were drawn from wave 7 (2020) of the German Ageing Survey (DEAS), a nationally representative study in Germany. Network, mediation, and binomial logistic regression analyses were performed to reveal the associations between feeling younger and biopsychosocial factors. Results: A total of 4,039 participants reported feeling younger, while 626 did not. Older chronological age, engaging in sports more frequently, a better standard of living, a better state of health, higher satisfaction with life, more positive attitudes towards one´s aging, and fewer depressive symptoms are associated with feeling younger in older people. Conclusion: The present study provides novel and consistent evidence regarding the association between feeling younger and biopsychosocial factors. Further research is needed to confirm these factors and identify how they can be adapted in potential intervention studies to generate the life and health circumstances that allow older people the benefit of feeling younger.